The role of working memory capacity in the integration of action preferences in fast decision-making in sport - Seidel-Marzi, O.; Cañal-Bruland, R. (Journal of Sports Sciences, 2025)
In dynamic and interactive sports, athletes are regularly provided with visual or verbal information about opponents` action preferences (AP) to support decision-making (DM). We examined whether differences in working memory capacity (WMC) moderate the effective use of AP information. Specifically, we tested whether higher visuospatial and verbal WMC is associated with better DM, and whether it facilitates the use of visually or verbally provided AP. After participants` (n = 48) visuospatial and verbal WMC were assessed, they performed a sport-specific DM task under time pressure without AP (Phase 1). Subsequently, they faced three experimental conditions with visually provided AP, verbally provided AP, or without AP in a counterbalanced order (Phase 2). Results of Phase 1 showed that WMC had no impact on overall DM performance, but that lower visuospatial WMC was associated with more accurate decisions, and both higher visuospatial and verbal WMC were associated with slower response times. When AP was provided (Phase 2), results showed no association between WMC and overall DM performance, but higher verbal WMC was associated with higher response accuracy when AP was provided verbally. We conclude that WMC may only play a subordinate role in the integration of AP in a fast DM.